2022
DOI: 10.2147/cmar.s350038
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Care During First Peruvian National Emergency COVID-19 Pandemic: A Multicentric Descriptive Study

Abstract: Purpose The aim of this study is to evaluate the oncological care during the first state of national emergency due to the COVID-19 pandemic in several public cancer hospitals in Peru. Materials and Methods A multicentric cross-sectional descriptive study was conducted by interviewing adult cancer patients diagnosed and treated between January 2019 and February 2020 from 18 hospitals. This study was carried out in September 2020, the last month of the first state of nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The COVID-19 pandemic has posed pressing challenges in providing health care to cancer patients (1).Due to lockdowns, a large part of screening and diagnosis has had to be postponed (2,3). During the pandemic, the cancer mortality rate was higher than that of the new coronary pneumonia (4), and an advanced clinical stage and treatment interruption were risk factors (5).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has posed pressing challenges in providing health care to cancer patients (1).Due to lockdowns, a large part of screening and diagnosis has had to be postponed (2,3). During the pandemic, the cancer mortality rate was higher than that of the new coronary pneumonia (4), and an advanced clinical stage and treatment interruption were risk factors (5).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of patients diagnosed and treated at the Instituto Nacional de Enfermedades Neoplasicas (INEN) has shown that 35.9% of BC patients were stages III or IV at diagnosis in 2000-2002; that figure did not significantly change in the 2010-2012 period, where 36.7% were diagnosed with advanced BC [22,23]. However, a recent study, conducted during the COVID-19 pandemic, has shown that 55.4% of cancer patients diagnosed and treated during 2019-2020 had an advanced stage [24]. In addition to the negative impact of COVID-19, the Peruvian healthcare system's inequities have worsened BC early detection.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these findings, a study in public cancer hospitals in Peru found that of the 98 patients who died: 73.5% died from cancer progression, 18.4% from COVID-19, and 8.1% from undetermined causes; advanced disease stage and discontinuation of therapy were risk factors. [ 24 ]. A cohort study in Belgium found an excess of 50 prostate cancer deaths and an expected excess of 105 deaths in April 2020 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort study in England found excess 1-year mortalities in prostate cancer patients during the COVID-19 pandemic [ 25 ]. Similarly, since the lockdown was introduced across Peru in 2020, considering the overstretched health care system, rescheduling of treatments and diagnostic procedures in oncological patients occurred [ 10 , 24 ]. There was an increase in the mortality rate of prostate cancer compared to previous years because of this, and, hence, an excess of mortality from prostate cancer.…”
Section: Discussionmentioning
confidence: 99%